2009
DOI: 10.1002/art.24608
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of psoriatic arthritis in people with psoriasis

Abstract: Objective. To determine the prevalence of psoriatic arthritis (PsA) using the ClASsification criteria for Psoriatic ARthritis (CASPAR) for classification. Methods. People with psoriasis were identified from the computerized morbidity indices of 2 large UK general practices, total population 22,500. Questionnaires were mailed to all 633 patients thus identified. Of the respondents, a 50% sample was assessed clinically and a proportion had blood samples and radiographs taken. Patients labeled as having psoriasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
115
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(131 citation statements)
references
References 42 publications
7
115
1
6
Order By: Relevance
“…PsA was reported in 21% of the overall MAPP patient population, which is generally consistent with published prevalence estimates [4,12,16,25,28].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…PsA was reported in 21% of the overall MAPP patient population, which is generally consistent with published prevalence estimates [4,12,16,25,28].…”
Section: Discussionsupporting
confidence: 88%
“…The clinical presentation of PsA varies. It occurs in approximately 30% of patients with psoriasis [4,12,16,25,28] and typically follows the onset of psoriasis by approximately 8-10 years [12,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Generally, laboratory tests are unhelpful: markers of systemic inflammation, such as the C-reactive protein or erythrocyte sedimentation rate, may be elevated in only 50% of cases and low titre rheumatoid factor and anti-cyclic citrullinated peptide may be found in up to 10% of cases. 4 Current National Institute for Health and Care Excellence guidance for the management of psoriasis suggests that the Psoriasis Epidemiology Screening Tool patient-completed screening questionnaire 12 ( www.bad.org. uk/healthcare-professionals/forms-downloads ) should be used annually to identify PsA.…”
Section: Diagnosismentioning
confidence: 99%
“…Psoriasis is a relatively common disease, affecting about 2 % of the general population; up to 25 % of these patients develop PsA about 10 years after the development of skin disease [1]. Increasing knowledge about the pathophysiology of psoriasis and PsA has revealed that the diverse disease manifestations observed in these disorders may share common immunologic and inflammatory pathways.…”
Section: Introductionmentioning
confidence: 99%